Sulfasalazine-double stranded ribonucleic acid nanoparticle for controlling Aedes aegypti mosquitoes - Subaraja, Mamangam; Hillary, V Edwin; Savarimuthu, Ignacimuthu (Journal of vector borne diseases, 2025)
Background & objectives: Aedes aegypti mosquitoes are vectors for dengue, Zika, chikungunya, and yellow fever viruses, which threaten over half the world's population. Therefore, new techniques are needed to control vector mosquitoes. The present study aimed to control female Ae. aegypti by targeting 3β-hydroxysteroid dehydrogenase (3β-HSD) and ecdysone receptor (EcR), which could potentially disrupt egg development, using sulfasalazine (SSZ)-double-stranded RNA (ds-RNA) nanoparticles (NPs). Methods: The SSZ-dsRNA NPs are characterized by light microscopy, field emission scanning electron microscopy, atomic force microscopy, raman spectroscopy, and fourier-transform infrared spectroscopy analysis. Next, 40 pl of SSZ, dsRNA, and SSZ-dsRNA NPs individually were injected into eggs of Ae. aegypti. Finally, the temporal gene expression levels of 3β-HSD and EcR genes were assessed using quantitative reverse transcription polymerase chain reaction (qRT-PCR). Results: The mortality rate and sterility were significantly increased (p<0.05), and the percentage of fecundity and viable progeny (p<0.05) showed effective results when exposed to SSZ-dsRNA compared to control eggs. In addition, the Sf9 cell line also confirmed the downregulation of the m-RNA 3β-HSD and EcR successfully when exposed to SSZ-dsRNA. Interpretation & conclusion: The current study proves for the first time that SSZ-dsRNA NPs can be used broadly for 3β-HSD and EcR gene silencing in mosquitoes. The use of this NPs SSZ-dsRNA complex in mosquito eggs leads to reduced fecundity in Ae. aegypti. This method will open a new door for mosquito control, which can be explored and utilized with future comprehensive research for better results. This method is not only limited to mosquito species like Ae. aegypti, it can also be tried with different mosquitoes as well as other insect species that cause harm to humans as pests of crops or vectors of various diseases.